2016
DOI: 10.1111/sji.12495
|View full text |Cite
|
Sign up to set email alerts
|

Immune Response of Healthy Adults to the Ingested Probiotic Lactobacillus casei Shirota

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 90 publications
1
29
0
Order By: Relevance
“…Administration of VSL#3 in our study led to a decrease in the production of various cytokines (IL-6, TNF, IL-10) in ex-vivo LPS-stimulated whole-blood cultures. In a recent study, ingestion for 4 weeks of a probiotic that contained Lactobacillus casei led to a reduction in the frequency of IL-6-producing monocytes on ex-vivo LPS stimulation [ 36 ]. However, in some older studies, supplementation with lactobacilli in healthy adults had no effect on IL-6 production on LPS stimulation [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Administration of VSL#3 in our study led to a decrease in the production of various cytokines (IL-6, TNF, IL-10) in ex-vivo LPS-stimulated whole-blood cultures. In a recent study, ingestion for 4 weeks of a probiotic that contained Lactobacillus casei led to a reduction in the frequency of IL-6-producing monocytes on ex-vivo LPS stimulation [ 36 ]. However, in some older studies, supplementation with lactobacilli in healthy adults had no effect on IL-6 production on LPS stimulation [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Probiotics may influence and enhance innate and adaptive immune response 4 . Several studies have reported the immune-modulatory effects of probiotics in humans 5 , 6 . Reduction in the production of inflammatory cytokines 7 , 8 and elevation of intestinal secretory immunoglobulin A (sIgA) were also reported by probiotics administration 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Harbige et al reported that daily ingestion of a probiotic drink containing Lactobacillus casei strain Shirota increased the salivary IgA1 and IgA2 concentrations in healthy adults. The B‐cell isotype switch to IgA production is controlled by transforming growth factor (TGF)‐β; therefore, it is possible that L. casei strain Shirota induce the production of IgA1 and IgA2 via TGF‐β induction . Further, intake of combined probiotics comprising L. casei and Enterococcus faecalis significantly increased the expression level of TGF‐β in the piglet jejunum in another study .…”
Section: Discussionmentioning
confidence: 97%
“…The B-cell isotype switch to IgA production is controlled by transforming growth factor (TGF)β; therefore, it is possible that L. casei strain Shirota induce the production of IgA1 and IgA2 via TGFβ induction. 27 Further, intake of combined probiotics comprising L. casei and Enterococcus faecalis significantly increased the expression level of TGFβ in the piglet jejunum in another study. 28 In the present study, it can be speculated that the intake of yogurt fermented with L. bulgaricus OLL1073R-1 may also activate the gut mucosal immune system and increase the expression levels of cytokines in the gut.…”
Section: Effects On Mucous Immunity By Intake Of Yogurt Fermented Wmentioning
confidence: 89%